2015
DOI: 10.1097/md.0000000000000951
|View full text |Cite
|
Sign up to set email alerts
|

D-Dimer Can Serve as a Prognostic and Predictive Biomarker for Metastatic Gastric Cancer Treated by Chemotherapy

Abstract: Systemic activation of hemostasis and thrombosis has been implicated in tumor progression and metastasis. D-dimer has been used as an indicator for the thrombosis. Here, we investigated the role of the activation of coagulation in patients with metastatic gastric cancer by measuring D-dimer level.We conducted an observation study of 46 metastatic gastric cancer patients who received palliative chemotherapy (CTx). D-dimer levels were assessed before CTx and at the first response evaluation after CTx.The overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 26 publications
3
45
0
Order By: Relevance
“…Previous studies have reported that high levels of plasma fibrinogen and/or D‐dimer are associated with poor prognosis in several solid malignancies . In this study, we found a significantly increased risk of disease progression and death in HCC patients with hyperfibrinogenemia.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Previous studies have reported that high levels of plasma fibrinogen and/or D‐dimer are associated with poor prognosis in several solid malignancies . In this study, we found a significantly increased risk of disease progression and death in HCC patients with hyperfibrinogenemia.…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies have reported that plasma fibrinogen and/or D‐dimer levels can predict poor prognosis in several types of malignancies including ovarian, breast, colorectal, lung, gastric, and pancreatic cancer . In lung cancer, plasma fibrinogen and D‐dimer levels have been shown to be associated with tumor pathological stage, response to therapy, and survival .…”
Section: Introductionmentioning
confidence: 99%
“…B). Moreover, cancer cells activate monocytes, macrophages, and platelets, which adhere to tumor cells and facilitate tumor growth and metastasis . There is a complex interplay between platelet‐induced tumor growth and tumor cell–induced platelet activation, with the involvement of multiple components within the tumor microenvironment that enhance metastasis .…”
Section: Coagulation In Malignancies and Some Implications For Therapmentioning
confidence: 99%
“…D-dimer, the final stable product of fibrin, which elevated after enhanced activation of Coagulation and fibrinolysis system, widely used in detect and exclude deep vein thrombosis and associated thromboembolic diseases [68]. Recent years, several studies reported that plasma D-dimer elevated in malignant tumors and its expression levels positively correlates with an advanced tumor stage, overall survival and therapy response [916]. In our previous study in GC patients, we found, D-dimer can better predict asymptomatic visceral metastasis than FIB and other factors [16].…”
Section: Introductionmentioning
confidence: 99%